ANALISIS KESALAHAN BERBAHASA PADA BALIHO CALON ANGGOTA LEGISLATIF DI KECAMATAN SAMBAS TAHUN 2024 SERTA RELEVANSINYA PADA PEMBELAJARAN BAHASA INDONESIA DI MADRASAH TSANAWIYAH - Sri Wahyuni; Dewi Ferawati, H. Syafiudin (ADISAM PUBLISHER, 2025)
This study aims to find out and obtain information related to language errors on legislative candidate billboards in Sambas District and how to correct these errors, as well as their relevance to Indonesian language learning at MTS Baitul Quran. This study uses a qualitative approach with a descriptive research type. The data collection technique uses documentation. The data source in this study is the 2024 legislative candidate billboards in Sambas District. The data is in the form of words and sentences contained in the data source. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validity technique used is observation persistence. The results of the study concluded that: First, there are language errors on the legislative candidate billboards in Sambas District, including: a. Errors in the use of capital letters as many as 8 data. b. Errors in the use of italics as many as 7 data, c. Errors in writing periods in the title name as many as 7 data. d. Errors in the use of exclamation marks as many as 4 data. e. Errors in writing standard marks as many as 3 data, Second Research on language errors on billboards of legislative candidates in Sambas District were corrected in accordance with the current language rules. Guided by the Enhanced Spelling Book (EYD) and the Big Indonesian Dictionary (KBBI) and other supporting documents relevant to the research. The forms of correction are as follows: a. Correction of errors in the use of capital letters as many as 8 data. b. Correction of errors in the use of italics as many as 7 data, c. Correction of errors in writing periods in titles as many as 7 data. d. Correction of errors in the use of exclamation marks as many as 4 data. e. Correction of errors in writing standard marks as many as 3 data, Third research on language errors on billboards of legislative candidates in Sambas District in 2024 is relevant to learning Indonesian at MTs, namely advertising materials. This is relevant to the implementation of the 2013 curriculum, which is stated in the RPP in basic competency point 3.4. and learning objectives